(untitled) (Horizontes de Enfermería, 2024)
The objective of this study was to describe the preventive measures for Sudden Infant Death Syndrome (SIDS) applied to a group of adolescent mothers. The applied methodology was a descriptive, transversal, and quantitative study. Fifty adolescent mothers of infants were studied through a questionnaire on sociodemographic data, health, and preventive measures. The results obtained were: only 30% of mothers know about SIDS, 38% of mothers use the prone position and 48% use the side position to put the infant to sleep, 16% of cohabitants smoke, and 30% drink alcohol. Finally, it was observed that, in general, mothers create an unsafe environment for infant sleep (use of padding, excessive blankets, and stuffed animals); it was concluded that adolescent mothers do not carry out preventive measures, which may represent a risk for infants. For the above reasons, it is recommended to emphasize SIDS prevention measures in this particular population.